A diagnostic platform for rapid, simultaneous quantification of procalcitonin and C-reactive protein in human serum. - Cao,XE; Ongagna-Yhombi,SY; Wang,R; Ren,Y; Srinivasan,B; Hayden,JA; Zhao,Z; Erickson,D; Mehta,S (EBioMedicine, 2022)
BACKGROUND: Early and accurate determination of bacterial infections as a potential cause for a patient's systemic inflammatory response is required for timely administration of appropriate treatment and antibiotic stewardship. Procalcitonin (PCT) and C-reactive protein (CRP) have both been used as biomarkers to infer bacterial infections, particularly in the context of sepsis. There is an urgent need to develop a platform for simultaneous quantification of PCT and CRP, to enable the potential use of these biomarkers at the point-of-care. METHODS: A multiplexed lateral flow assay (LFA) and a fluorescence optical reader were developed. Assay performance was validated by testing spiked antigens in the buffer, followed by a validation study comparing results with conventional assays (Roche Cobas e411 Elecsys PCT and Siemens ADVIA XPT CRP) in 25 archived remnant human serum samples. FINDINGS: A linear regression correlation of 0·97 (P < 0·01) was observed for PCT, and a correlation of 0·95 (P < 0·01) was observed for CRP using direct patient samples. We also validated our platform's ability to accurately quantify high-dose CRP in the hook effect range where excess unlabeled analytes occupy binding sites at test lines. INTERPRETATION: A fluorescence reader-based duplex LFA for simultaneous quantification of PCT and CRP was developed and successfully validated with clinical samples. The rapid, portable, and low-cost nature of the platform offers potential for differentiation of bacterial and viral infections in emergency and low-resource settings at the point-of-care. FUNDING: NIH/NIBIB Award 1R01EB021331, and Academic Venture Fund from the Atkinson Center for a Sustainable Future at Cornell University.